2017
DOI: 10.1521/pedi_2016_30_254
|View full text |Cite
|
Sign up to set email alerts
|

Experts’ Views Regarding the Conceptualization of Narcissism

Abstract: There is debate over the definition of narcissism across social/personality and clinical psychology. The current article aims to quantify the level of disagreement by measuring experts' opinions concerning the attributes most central to narcissism. Accordingly, we developed a comprehensive list of attributes associated with narcissism and had 49 self-identified experts (among them 17 women, 23 psychologists from clinical psychology and 22 from social/personality psychology) rate these characteristics and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 29 publications
(49 reference statements)
2
55
0
Order By: Relevance
“…Conventional psychological and diagnostic descriptions of narcissism, e.g., the Narcissistic Personality Inventory [24] or the Diagnostic Statistical Manual (DSM) [25], tend to overemphasize grandiose aspects of narcissism [26-28]. In a recent study, this description has been shown to be consistent with the view of experts who consider grandiose traits as NPD core pathology [17, 29]. …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Conventional psychological and diagnostic descriptions of narcissism, e.g., the Narcissistic Personality Inventory [24] or the Diagnostic Statistical Manual (DSM) [25], tend to overemphasize grandiose aspects of narcissism [26-28]. In a recent study, this description has been shown to be consistent with the view of experts who consider grandiose traits as NPD core pathology [17, 29]. …”
Section: Introductionmentioning
confidence: 93%
“…Although it is considered as particularly difficult to treat, studies of this comorbidity are limited [14, 15]. Even less research has been done on subthreshold narcissistic traits in BPD [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This attention to the multidimensionality of narcissism was associated with a variety of interesting programs of research on the measurement (Back et al, ; Glover, Miller, Lynam, Crego, & Widiger, ; Roche, Pincus, Lukowitsky, Menard, & Conroy, ), correlates (Miller, Lynam, Hyatt, & Campbell, in press; Morf et al, in press), and dynamics of narcissism (Back et al, ; Geukes et al, ; Leckelt, Küfner, Nestler, & Back, ; Lukowitsky & Pincus, ; Roche, Pincus, Conroy, Hyde, & Ram, ). However, so far, no consensus has emerged regarding how the concept is meaningfully distinct from particular patterns of nomothetic traits (Ackerman et al, ). The issue that is implicit in this literature but rarely discussed is that identifying the core traits associated with narcissism is mostly not an empirical question.…”
Section: Personality Disorders As Traitsmentioning
confidence: 99%
“…Significant debate remains regarding the degree to which traits such as vulnerability and insecurity are core features of pathological narcissism . In narcissism research, traits such as insecurity and hypersensitivity reflect what has been called vulnerable narcissism, whereas traits such as arrogance and exhibitionism characterize grandiose narcissism .…”
Section: The Current Investigationmentioning
confidence: 99%